2010
DOI: 10.1016/j.physe.2009.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of diffusion thermopower in the quantum Hall systems

Abstract: We have measured diffusion thermopower in a two-dimensional electron gas at low temperature (T =40 mK) in the field range 0 < B < 3.4 T, by employing the current heating technique. A Hall bar device is designed for this purpose, which contains two crossing Hall bars, one for the measurement and the other used as a heater, and is equipped with a metallic front gate to control the resistivity of the areas to be heated. In the low magnetic field regime (B ≤ 1 T), we obtain the transverse thermopower S yx that qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Fujita et al [6] measured the 2DEG's contribution to these effects using the direct Joule heating of the 2DEG at a low temperature (∼0.04 K). They experimentally suggested that this Joule heating method raises only the electron temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujita et al [6] measured the 2DEG's contribution to these effects using the direct Joule heating of the 2DEG at a low temperature (∼0.04 K). They experimentally suggested that this Joule heating method raises only the electron temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The schematic diagram of the experimental system [6], including the Joule heating part, and the observed Nernst coefficient V yx by the method are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al 6 observed the Nernst voltage of a two-dimensional electron gas (2DEG) using the direct Joule heating method, by which they could accurately extract the electron behavior without the influence of phonon drag, at low temperature (40 mK). They found that an unusual Nernst voltage which is not theoretically expected appears under a strong magnetic field, B > 1.8 T. In a previous study, 7 we simulated the distributions of the temperature T and the voltage / of a 2DEG.…”
Section: Introductionmentioning
confidence: 99%
“…6 The cooling of the system is a complicated process, since it may be related to several thermoelectric and thermomagnetic phenomena. To clarify the mechanism of the cooling effect, we here numerically analyze the contributions of various effects.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by directly passing a moderately large current to a section of 2DEG designated to serve as a heater. 13,14 It will be practically very difficult, however, to apply this Joule heating technique to a Corbino device, since it requires the heating current to pass only along the outer (or inner) rim of the annularly patterned 2DEG. In the present study, we take an alternative approach, microwave irradiation, for the electron heating.…”
mentioning
confidence: 99%